Inorganic Pollutants in Edible Grasshoppers (Ruspolia nitidula) of Uganda and their Major Public Health Implications. - Keneth Iceland, Kasozi; Namazi, Catherine; Basemera, Elizabeth; Atuheire, Collins; Odwee, Ambrose; Majalija, Samuel; Kateregga, John N. (Kabale University, 2023)
Background: Inorganic contamination of food products is associated with adverse health effects, however, information on grasshoppers in Africa is sparse. The objective of the study was to determine antioxidant, heavy metal and food safety status of edible grasshoppers of Uganda. Methods: A cross-sectional study was conducted in central and southwestern Uganda, in which a questionnaire was administered to grasshopper harvesters. Grasshopper samples were collected from each harvesting point and analyzed in the laboratory for antioxidant and heavy metal content i.e. Lead (Pb), Chromium (Cr), Zinc (Zn) and Cadmium (Cd) using atomic absorbance spectrometric (AAS) method on the heads and abdomen of the insects. Results: Major antioxidants were Catalase > Glutathione > Glutathione peroxidase. In addition concentrations of heavy metals were in the order of Pb > Cr > Zn > Cd in the heads and abdomens of the grasshoppers. Pb concentrations were found to be higher in the heads than the abdomens and the carcinogenic potential of the grasshoppers was over 10 times over the recommended levels. Grasshoppers were found not to be safe especially in children due to their small body weight in comparison to adults. Conclusion: Pb poisoning in the Ugandan children would be propagated through contaminated grasshoppers. Keywords: Ecotoxicology, Food Safety, Metals, Insects, Nutritional Toxicology, Pb poisoning, Uganda.